Identification and Expression Analysis of Na+/K+-ATPase and NKA-Interacting Protein in Ark Shells - Man Song; Xiao Liu; Jie Zhang; Wuping Li; Jingfen Pan; Yanglei Jia (Biophysica, 2025)
Ark shells are a group of bivalves that exhibit extraordinary adaptability to the dual environmental pressures of low oxygen and osmotic imbalance. These challenges are particularly pronounced in intertidal zones, where organisms are subjected to rapid and drastic changes in their surroundings. This research investigated the molecular mechanisms that underpin their survival and adaptive strategies, with particular focused on sodium–potassium ATPase (NKA), a pivotal enzyme responsible for maintaining cellular ion transmembrane gradients and ensuring cellular homeostasis under stress conditions. By utilizing genome assemblies and transcriptomics datasets from multiple ark shell species, we successfully identified two distinct NKA-α subunits and two NKA-β subunits, which are essential components of the NKA complex. Moreover, the discovery of a conserved NKA-interacting protein (NKAIN) highlights the complexity and evolutionary significance of the NKA-NKAIN system in ark shells. Phylogenetic analysis revealed a high degree of conservation in the NKA-α and NKA-β subunits across ark shells, suggesting strong selective pressures to preserve their functionality. However, the marked divergence observed between the two NKA-β subunits suggests that they may serve distinct roles in ion transport, potentially specialized for specific environmental conditions or stress responses. Comparative transcriptomic analysis further revealed the regulatory roles of NKA and NKAIN in the adaptive responses to hypoxia and osmotic stress, showing that these genes are dynamically modulated at the transcriptional level in response to environmental challenges. These findings provide a molecular foundation for understanding the osmotic adaptation mechanisms in ark shells and offer novel insights into their ability to thrive in mudflat habitats. This comprehensive exploration of the NKA-NKAIN system not only enhances our understanding of the resilience of ark shells but also provides valuable insights into the molecular and physiological strategies employed by bivalves in intertidal environments.